Use of breathing exercises in physical education of students with health disabilities (Bangladesh Journal of Medical Science, 2025)
Background Preserving the health of the population is the priority task of the state. The health of the younger generation, including students, is now especially alarming. Recently, there has been a sharp increase in the number of students with various health conditions. Numerous studies in recent years indicate that the problem of deterioration of students’ health is still relevant. According to the results of annual medical examinations, more and more students at physical education class have to be assigned to special medical groups.Aim The objective of the study is to evaluate the effectiveness of the use of breathing exercises in physical education of students with health disorders.Methods Evaluation of the effectiveness of the method of application of breathing exercises according to the method of A.N. Strelnikova and “Bodyflex” by Greer Childers at PT training sessions with students with functional health disorders was carried out on the basis of the results of a comparative experiment conducted at the Department of Physical Education of Moscow Polytechnic University.Results Before the experiment, the average scores of EG students ranged from 3.0 to 5.0 points, and the average score in the group was 4.05 ± 0.1. After the experiment, the average scores of the students were in the range from 3.2 to 5.0 points, and the average score in the group was 4.14 ± 0.09 (the differences are not significant).Conclusion The results of the study have proved that the experimental method of using breathing exercises in physical education of students with health disorders contributes to the positive correction and improvement of the functional state of the cardiovascular and respiratory systems. It has also been found to have a positive effect on the well-being and academic achievements of the subjects.Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 239-245